The key metabolic genes and networks regulating the fruit acidity and flavonoid of Prunus mume revealed via transcriptomic and metabolomic analyses - Gao, Xuan; Wu, Shuangshuang; Lv, Guosheng; Wang, Mengyang; Li, Lingxiang; Liu, Yahui; He, Feng; Xiao, Jiaxin (Frontiers in Plant Science, 2025)
The acidic taste of Mei fruit (Prunus mume) is a major contributor to its quality, but its formation mechanism remains unclear. Here, we unraveled the networks of organic acid and flavonoid metabolism in two Mei fruit. The results showed that the differentially expressed genes were mainly concentrated in the processes of carbohydrate derivative binding, carboxylic acid, and organic acid metabolism. While the differentially accumulated metabolites were mainly associated with flavone and flavonol biosynthesis and amino acid and carbon metabolism. Moreover, we identified key metabolites, such as citric and succinic acids, which may be central to the development of acidity in Mei fruit, and determined that they are under the regulatory influence of specific genes, including galactinol-sucrose-galactosyltransferase 5, mitogen-activated protein kinase kinase kinase NPK1-like, glutamate receptor, and chalcone isomerase. Furthermore, transcription factors ERF027, bHLH92, bHLH35, and WRKY23 were identified as potential pivotal regulators within these networks. These results provide new insights into the metabolic regulation of acidity and flavonoid in Mei fruit.